Existence and Attractivity of Stationary Solutions of a Degenerate Diffusion Equation (Journal of Partial Differential Equations, 1993)
This paper is concerned with the existence and attractivity of the stationary solutions of a degenerate diffusion equation. By using monotone method and applying some special techniques, we extend the-results in 1-dimension case to higher dimension cases.